2021
DOI: 10.3390/nano11092234
|View full text |Cite
|
Sign up to set email alerts
|

Nanocurcumin-Loaded UCNPs for Cancer Theranostics: Physicochemical Properties, In Vitro Toxicity, and In Vivo Imaging Studies

Abstract: Formulation of promising anticancer herbal drug curcumin as a nanoscale-sized curcumin (nanocurcumin) improved its delivery to cells and organisms both in vitro and in vivo. We report on coupling nanocurcumin with upconversion nanoparticles (UCNPs) using Poly (lactic-co-glycolic Acid) (PLGA) to endow visualisation in the near-infrared transparency window. Nanocurcumin was prepared by solvent-antisolvent method. NaYF4:Yb,Er (UCNP1) and NaYF4:Yb,Tm (UCNP2) nanoparticles were synthesised by reverse microemulsion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Peaks at 492 and 626 cm −1 were assigned to the Na–F bonding vibrational frequencies. 27–29 Nevertheless, two dominant broad bands around 275 cm −1 and 745 cm −1 attributed to the cubic phase of NaYF 4 are not observed in all spectra. 30 An increase in Yb concentrations does not affect the crystal structure of NaYF 4 .…”
Section: Resultsmentioning
confidence: 80%
“…Peaks at 492 and 626 cm −1 were assigned to the Na–F bonding vibrational frequencies. 27–29 Nevertheless, two dominant broad bands around 275 cm −1 and 745 cm −1 attributed to the cubic phase of NaYF 4 are not observed in all spectra. 30 An increase in Yb concentrations does not affect the crystal structure of NaYF 4 .…”
Section: Resultsmentioning
confidence: 80%
“…Curcumin nanoparticles, functionalized with polymeric, metallic, or lipidic nanoparticles, can easily be carried across the membrane and released at the target. Curcumin loaded with biocompatible polyester-origin polymer poly(D,L-lactide), PLA, was used to study the stabilization and cytotoxicity, where the encapsulated nanocurcumin showed higher resistance to photobleaching as well as photodegradation [ 61 ]. Microscopic lamellar structures called niosomes can be loaded with metal nanoparticles, along with curcumin resulting in an enhanced drug delivery [ 62 , 63 ].…”
Section: Types Of Nanocarriers Used For Curcumin Deliverymentioning
confidence: 99%
“…In another research, nano curcumin was combined with rare-earth-doped upconversion nanoparticles (UCNPs). Poly (lactic-co-glycolic acid) (PLGA) was used to promote sustained drug delivery and drug release, targeting, minimizing the non-specific consumption by undesirable tissues, and enhancing its aqueous solubility ( 276 ). Curcumin -incorporated PLGA nanoparticles have exhibited increased cellular uptake, induction of apoptosis, suppression of tumor cell proliferation, and improvement in bioavailability.…”
Section: Future Prospectsmentioning
confidence: 99%
“…Curcumin -incorporated PLGA nanoparticles have exhibited increased cellular uptake, induction of apoptosis, suppression of tumor cell proliferation, and improvement in bioavailability. The advantage of combining UCNP and nano curcumin lies in the upconversion of visible light leading to the excitement of photosensitizer and favoring the fluorescence resonance energy transfer (FRET) which can be used in the examination of in vivo interaction between bimolecular entities ( 276 ).…”
Section: Future Prospectsmentioning
confidence: 99%